The measurement of labour content: A general approach - Naoki Yoshihara; Roberto Veneziani (University of Massachusetts, Department of Economics, 2017)
This paper analyses the theoretical issues related to the measurement of labour content for general technologies with heterogeneous labour. A novel axiomatic framework is used in order to formulate the key properties of the notion of labour content and analyse its theoretical foundations. The main measures of labour content used in various strands of the literature are then characterised. Quite surprisingly, a unique axiomatic structure can be identified which underlies measures of labour aggregates used in such diverse fields as neoclassical growth theory, input-output approaches, productivity analysis, and classical political economy.
Keywords: D57; J24; O33; D46; 330; labour content; labour productivity; technical change; axiomatic analysis